Ti-Al-Ta-Nb series alloy with low oxygen content as well as preparation method and application of Ti-Al-Ta-Nb series alloy
Through the ball mill mixing and sintering process, the reaction of rare earth elements with oxygen is used to change the oxygen distribution state, which solves the problem of excessive oxygen content of titanium alloys in powder metallurgy, improves the plasticity and strength of the alloy, and reduces the preparation cost.
Patent Information
- Application Number
- CN202510045755.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-11
AI Technical Summary
When preparing titanium alloys, it is difficult to avoid the introduction of oxygen when the powder metallurgy method is used, resulting in excessive oxygen content in the alloy and affecting its plasticity.
The preparation method of low-oxygen content Ti-Al-Ta-Nb alloy is adopted to prepare raw materials by mixing ball mills, perform cold isostatic molding, program heating sintering and cooling, and use rare earth elements to react with oxygen to change the distribution state of oxygen, and convert from solid solution to solid solution + aggregate state.
It significantly reduces the oxygen content in the alloy, improves the plasticity of the alloy, and takes into account high strength and low preparation cost.
Smart Images

Figure CN119800154A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloys, and in particular to a Ti-Al-Ta-Nb alloy with low oxygen content and a preparation method and application thereof. Background Art
[0002] Titanium-aluminum-niobium-tantalum alloys are widely used in aerospace, defense and military fields due to their high specific strength, good corrosion resistance, high temperature resistance and excellent creep performance. Powder metallurgy is a common processing method for titanium alloys. It often uses metal powder as raw material and sintering at a specific temperature to ensure that the metal powder can be fully diffused, thereby preparing an alloy with uniform composition. In addition, powder metallurgy, as a near-net forming technology, can significantly reduce the amount of machining of the alloy, greatly improve the powder utilization rate, and thus reduce the production cost of the alloy.
[0003] However, the preparation of titanium alloys by powder metallurgy inevitably introduces oxygen. Specifically, there are three main aspects of oxygen introduction: first, oxygen adsorbed on the surface of the powder, second, oxides formed on the surface of the powder, and third, protective gas introduced during sintering and residual oxygen in the vacuum furnace. During the sintering process, this oxygen will gradually diffuse into the lattice gap of Ti. As a strong stabilizing element of α-Ti, excessive oxygen content can easily make the alloy brittle, which is not conducive to the plasticity of the alloy. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a low-oxygen content Ti-Al-Ta-Nb alloy and its preparation method and application. The Ti-Al-Ta-Nb alloy provided by the present invention has a uniform and dense structure, a low oxygen content, and the distribution state of oxygen is changed from a solid solution state to a solid solution + aggregation state. The alloy has high strength and greatly improved plasticity.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a Ti-Al-Ta-Nb alloy with low oxygen content. The composition range of the Ti-Al-Ta-Nb alloy with low oxygen content is Ti-(0-15)Al-(5-35)Nb-(5-20)Ta-(0-5)Ce-(0-5)Y-(0-5)La in terms of mass percentage. The contents of rare earth elements in the Ti-Al-Ta-Nb alloy with low oxygen content are not all 0 at the same time, and the total content of rare earth elements does not exceed 5% of the total mass of the alloy.
[0007] The low oxygen content Ti-Al-Ta-Nb alloy comprises the following raw materials in percentage by weight:
[0008]
[0009]
[0010] Preferably, the particle size of the Ti powder is 20 to 50 μm;
[0011] The particle size of the Nb powder is 5 to 20 μm;
[0012] The particle size of the Ta powder is 5 to 20 μm.
[0013] Preferably, the mass content of Nb in the Al-Nb alloy powder is 50-70%, and the balance is Al;
[0014] The particle size of the Al-Nb alloy powder is 20-50 μm.
[0015] Preferably, the rare earth hydride is one or more of YH3, YH2, LaH3, LaH2, CeH3 and CeH2;
[0016] The particle size of the rare earth hydride powder is 10 to 100 μm.
[0017] Preferably, the rare earth element powder is one or more of Y powder, La powder and Ce powder;
[0018] The particle size of the rare earth element powder is 10 to 100 μm.
[0019] Preferably, in terms of mass percentage, the Al-Ce-La alloy powder comprises: Ce: 40-50wt.%; Al: 20-30wt.%; La: 20-30wt.%.
[0020] Preferably, the particle size of the Al-Ce-La alloy powder is 10 to 50 μm.
[0021] The present invention provides a method for preparing the above-mentioned low-oxygen content Ti-Al-Ta-Nb alloy, comprising the following steps:
[0022] The raw materials for preparing the low-oxygen content Ti-Al-Ta-Nb alloy are ball-milled and mixed to obtain a mixed powder;
[0023] The mixed powder is subjected to cold isostatic pressing, programmed temperature sintering and cooling in sequence to obtain a Ti-Al-Ta-Nb alloy with low oxygen content.
[0024] Preferably, the pressure of the cold isostatic pressing is 300-400 MPa, and the holding time is 20-60 min.
[0025] Preferably, the programmed temperature sintering is carried out under a protective atmosphere;
[0026] The temperature rising program of the programmed temperature rising sintering comprises:
[0027] Raising the temperature from room temperature to a first temperature at a rate of 5 to 10°C / min;
[0028] Raise the temperature from the first temperature to the sintering temperature at 2-5°C / min and keep the temperature;
[0029] The first temperature is 1000-1200° C., the sintering temperature is 1300-1550° C., and the insulation time is 2-5 hours.
[0030] The invention provides a Ti-Al-Ta-Nb alloy with low oxygen content. The composition range of the Ti-Al-Ta-Nb alloy with low oxygen content is Ti-(0-15)Al-(5-35)Nb-(5-20)Ta-(0-5)Ce-(0-5)Y-(0-5)La in terms of mass percentage. The contents of rare earth elements in the Ti-Al-Ta-Nb alloy with low oxygen content are not all 0 at the same time, and the total content of rare earth elements does not exceed 5% of the total mass of the alloy. The Ti-Al-Ta-Nb alloy with low oxygen content comprises the following raw materials in terms of mass percentage: 25-90% of Ti powder; 0-15% of Al-Nb alloy powder; 0-35% of Nb powder; 5-20% of Ta powder; 0-5% of rare earth hydride powder or rare earth element powder; and 0-5% of Al-Ce-La alloy powder. The present invention uses rare earth alloy powder (Al-Ce-La) alloy powder or rare earth single substance (Y, La, Ce) or rare earth hydride (YH3, YH2, LaH3, LaH2, CeH3, CeH2) as a rare earth source. During the alloy sintering process, the rare earth elements in the rare earth source react with the oxygen in the metal powder to form oxides, which can change the distribution of oxygen in the alloy, so that the oxygen is transformed from a solid solution state to a solid solution + aggregation state, and the oxygen content dissolved in the alloy phase is greatly reduced. The low-oxygen content Ti-Al-Ta-Nb alloy of the present invention has a uniform and dense structure, low preparation cost, and greatly improved plasticity while taking into account high strength. The results of the embodiment show that the distribution state of oxygen in the low-oxygen content Ti-Al-Ta-Nb alloy of the present invention is transformed from a solid solution state to a solid solution + aggregation state, and the overall oxygen content is reduced by about 12.2%. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The distribution diagrams of oxygen and other elements of the alloys obtained in Example 1 and Comparative Example 1;
[0032] Figure 2 is the oxygen content in the alloys obtained in Example 1 and Comparative Example 1;
[0033] Figure 3 The static compressive stress-strain curves of the alloys obtained in Example 1 and Comparative Example 1 are shown.
[0034] Figure 4The distribution diagram of oxygen and other elements in the alloy obtained in Example 2;
[0035] Figure 5 This is the static compressive stress-strain curve of the alloy obtained in Example 2.
[0036] Figure 6 The distribution diagram of oxygen and other elements in the alloy obtained in Example 3;
[0037] Figure 7 This is the static compressive stress-strain curve of the alloy obtained in Example 3. DETAILED DESCRIPTION
[0038] The present invention provides a Ti-Al-Ta-Nb alloy with low oxygen content. The composition range of the Ti-Al-Ta-Nb alloy with low oxygen content is Ti-(0-15)Al-(5-35)Nb-(5-20)Ta-(0-5)Ce-(0-5)Y-(0-5)La in terms of mass percentage. The contents of rare earth elements in the Ti-Al-Ta-Nb alloy with low oxygen content are not 0 at the same time, and the total content of rare earth elements does not exceed 5% of the total mass of the alloy.
[0039] In the present invention, the low oxygen content Ti-Al-Ta-Nb alloy includes 0-15% Al, preferably 1-12%, and more preferably 5-10% Al, in terms of mass percentage. As a specific embodiment of the present invention, the Al content in the low oxygen content Ti-Al-Ta-Nb alloy is 0%, 2%, 4%, 6%, 8%, 10%, 12%, 14% or 15%. In the present invention, the Al element reacts with Ti to form an intermetallic compound to provide strength to the alloy.
[0040] In the present invention, the low oxygen content Ti-Al-Ta-Nb alloy includes 5-35% Nb, preferably 10-30%, and more preferably 15-18% by mass percentage. As a specific embodiment of the present invention, the content of Nb in the low oxygen content Ti-Al-Ta-Nb alloy is 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 30% or 35%. In the present invention, Nb is a β-phase stabilizing element. On the one hand, it can improve the plasticity of the alloy. On the other hand, Nb will react with Ti and Al to form intermetallic compounds with higher strength. Therefore, Nb can adjust the strength and plasticity of the alloy.
[0041] In the present invention, the low oxygen content Ti-Al-Ta-Nb alloy includes 5-20% Ta, preferably 12-18%, and more preferably 15%, in terms of mass percentage. As a specific embodiment of the present invention, the content of Ta in the low oxygen content Ti-Al-Ta-Nb alloy is 5%, 10%, 12%, 14%, 15%, 16%, 18% or 20%. In the present invention, Ta is a high melting point refractory metal with good high temperature performance. It can form a solid solution with Ti to improve the high temperature performance of the alloy. In addition, Ta is also a β phase stabilizing element and can regulate the plasticity of the alloy.
[0042] In the present invention, the low oxygen content Ti-Al-Ta-Nb alloy includes 0-5% Ce, preferably 1-4% Ce, in terms of mass percentage. As a specific embodiment of the present invention, the Ce content in the low oxygen content Ti-Al-Ta-Nb alloy is 0%, 1%, 2%, 3%, 4% or 5%.
[0043] In the present invention, the low oxygen content Ti-Al-Ta-Nb alloy includes 0-5% Y, preferably 1-4% by mass. As a specific embodiment of the present invention, the content of Y in the low oxygen content Ti-Al-Ta-Nb alloy is 0%, 1%, 2%, 3%, 4% or 5%.
[0044] In the present invention, the low oxygen content Ti-Al-Ta-Nb alloy includes 0-5% La, preferably 1-4% La, in terms of mass percentage. As a specific embodiment of the present invention, the content of La in the low oxygen content Ti-Al-Ta-Nb alloy is 0%, 1%, 2%, 3%, 4% or 5%.
[0045] In the present invention, the low oxygen content Ti-Al-Ta-Nb alloy comprises the following raw materials in percentage by mass:
[0046]
[0047] Unless otherwise specified, the raw materials used in the present invention are all commercially available.
[0048] In the present invention, the raw material for preparing the low oxygen content Ti-Al-Ta-Nb alloy includes 25-90% Ti powder, preferably 40-65%, more preferably 45-60%, by mass percentage. As a specific embodiment of the present invention, the amount of the Ti powder is 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 80% or 90%. In the present invention, the particle size of the Ti powder is preferably 20-50 μm, more preferably 30-50 μm, and further preferably 40 μm.
[0049] In the present invention, the raw materials for preparing the low oxygen content Ti-Al-Ta-Nb alloy include 0-15% Al-Nb alloy powder, preferably 5-10%, in terms of mass percentage. As a specific embodiment of the present invention, the amount of the Al-Nb alloy powder is 0%, 5%, 8%, 10%, 12% or 15%. In the present invention, the mass content of Nb in the Al-Nb alloy powder is preferably 50-70%, more preferably 60%, and the balance is Al. In the present invention, the particle size of the Al-Nb alloy powder is preferably 20-50μm, more preferably 20-40μm, and further preferably 30μm. The present invention uses Al-Nb alloy as raw material, which can promote the densification of the alloy during the sintering process, and at the same time promotes the uniform diffusion of elements and improves the overall mechanical properties of the alloy.
[0050] In the present invention, the raw material for preparing the low oxygen content Ti-Al-Ta-Nb alloy includes 0-35% Nb powder, preferably 5-30%, more preferably 10-20%, by mass percentage. As a specific embodiment of the present invention, the amount of the Nb powder is 0%, 5%, 8%, 10%, 12%, 15%, 20%, 25%, 30% or 35%. In the present invention, the particle size of the Nb powder is preferably 5-20 μm, more preferably 5-10 μm.
[0051] In the present invention, the raw material for preparing the low oxygen content Ti-Al-Ta-Nb alloy includes 5-20% Ta powder, preferably 10-15%, by mass percentage. As a specific embodiment of the present invention, the amount of Ta powder is 5%, 8%, 10%, 12%, 15% or 20%. In the present invention, the particle size of the Ta powder is preferably 5-20 μm, more preferably 5-10 μm.
[0052] In the present invention, the raw materials for preparing the low oxygen content Ti-Al-Ta-Nb alloy include 0-5% rare earth hydride powder or rare earth element powder, preferably 1-4%, more preferably 2-3%, by mass percentage. In the present invention, the rare earth hydride is preferably one or more of YH3, YH2, LaH3, LaH2, CeH3 and CeH2; the particle size of the rare earth hydride powder is preferably 10-100 μm, more preferably 10-50 μm, and further preferably 20-40 μm.
[0053] In the present invention, the rare earth powder is preferably one or more of Y powder, La powder and Ce powder; the particle size of the rare earth powder is preferably 10 to 100 μm, more preferably 10 to 50 μm, and further preferably 20 to 40 μm.
[0054] In the present invention, the raw material for preparing the low oxygen content Ti-Al-Ta-Nb alloy includes 0-5% Al-Ce-La alloy powder, more preferably 1-4%, and further preferably 2-3%, by mass percentage. In the present invention, the composition of the Al-Ce-La alloy powder preferably includes: Ce: 40-50wt.%; Al: 20-30wt.%; La: 20-30wt.%. In the present invention, the particle size of the Al-Ce-La alloy powder is preferably 10-50μm, more preferably 20-40μm.
[0055] In the present invention, the amounts of the rare earth hydride powder, the rare earth element powder and the Al-Ce-La alloy powder are not all 0 at the same time, and the total content of the rare earth elements does not exceed 5% of the total mass of the alloy.
[0056] The present invention provides a method for preparing the above-mentioned low-oxygen content Ti-Al-Ta-Nb alloy, comprising the following steps:
[0057] The raw materials for preparing the low-oxygen content Ti-Al-Ta-Nb alloy are ball-milled and mixed to obtain a mixed powder;
[0058] The mixed powder is subjected to cold isostatic pressing, programmed temperature sintering and cooling in sequence to obtain a Ti-Al-Ta-Nb alloy with low oxygen content.
[0059] The present invention ball-mills and mixes the raw materials for preparing the low-oxygen content Ti-Al-Ta-Nb alloy to obtain a mixed powder. In the present invention, the ball milling medium of the ball milling mixture is preferably Ar gas, and the present invention avoids oxidation of the powder by ball milling under Ar gas. In the present invention, the ball-to-material ratio of the ball milling mixture is preferably 3 to 5:1. In the present invention, the time of the ball milling mixture is preferably 60 to 90 minutes. As a specific embodiment of the present invention, the time of the ball milling mixture is 60 minutes, 70 minutes, 80 minutes or 90 minutes. In the present invention, the rotation speed of the ball milling mixture is preferably 200 to 300 r / min. As a specific embodiment of the present invention, the rotation speed of the ball milling mixture is 200 r / min, 240 r / min, 280 r / min or 300 r / min.
[0060] After obtaining the mixed powder, the present invention sequentially performs cold isostatic pressing, programmed temperature sintering and cooling on the mixed powder to obtain a Ti-Al-Ta-Nb alloy with a low oxygen content. In the present invention, the pressure of the cold isostatic pressing is preferably 300-400 MPa, more preferably 350 MPa, and the holding time is preferably 20-60 min, more preferably 30-50 min.
[0061] In the present invention, the temperature-raising program of the programmed temperature-raising sintering preferably includes:
[0062] Raising the temperature from room temperature to a first temperature at a rate of 5 to 10°C / min;
[0063] The temperature is raised from the first temperature to the sintering temperature at a rate of 2 to 5°C / min and then maintained.
[0064] In the present invention, the programmed temperature sintering is preferably carried out in a tube furnace. In the present invention, the programmed temperature sintering is preferably carried out in an Ar atmosphere. In the present invention, during the programmed temperature sintering, the Ar gas flow rate is preferably 100 to 200 mL / min.
[0065] In the present invention, before the temperature is raised from room temperature to the first temperature at a rate of 5 to 10°C / min, the present invention preferably repeatedly evacuates the furnace three times to ensure that the vacuum degree in the furnace is reduced to less than 4×10 -3 Pa, and then flow Ar gas into the furnace to stabilize the gas pressure in the furnace at 101 kPa. In the present invention, the first temperature is preferably 1000-1200°C, more preferably 1050-1150°C; the sintering temperature is preferably 1300-1550°C, more preferably 1400-1500°C; the insulation time is preferably 2-5h, more preferably 3-4h. The present invention can obtain a dense and uniformly distributed alloy through the programmed temperature sintering. The protective gas during the programmed temperature increase process and repeated vacuuming before sintering can reduce the oxygen content in the sintering atmosphere, thereby reducing the oxygen content in the alloy.
[0066] In the present invention, the cooling is preferably furnace cooling.
[0067] The low oxygen content Ti-Al-Ta-Nb alloy provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0068] Example 1
[0069] Alloy composition: (Ti-5Nb-15Ta)-1.5Y (mass fraction, %)
[0070] The preparation method adopts the following steps:
[0071] (1) Weigh Ti powder, Nb powder, Nb powder, Ta powder and YH2 in proportion, the mass percentage of which is: Ti powder 78.5%, Nb powder 5%, Ta powder 15%, YH2 powder 1.5%, among which the particle size of Ti powder is 45μm, the particle size of Nb alloy powder is 10μm, the particle size of Ta powder is 10μm, and the particle size of YH2 powder is 20μm.
[0072] (2) Ar was used as the ball milling medium, and the mass ratio of grinding balls to powders was 3:1. Ti powder, Nb alloy powder, Ta powder and YH2 powder were fully mixed using a planetary ball mill at a speed of 300 r / min for 60 min.
[0073] (3) The powder obtained in step (2) is placed in a rubber mold for cold isostatic pressing at a molding pressure of 300 MPa and a holding time of 30 min.
[0074] (4) The titanium alloy compact obtained in step (3) is placed in a sintering furnace for programmed heating, and the vacuum degree in the furnace is reduced to 2×10 -3 Pa, after the flowing Ar gas is introduced until the pressure in the furnace is stabilized at 101 kPa, the Ar gas flow rate is maintained at a constant value of 200 mL / min, and the green compact is heated from room temperature to 1200°C at a heating rate of 10°C / min;
[0075] In the flowing Ar atmosphere, the sample was heated from 1200° C. to 1500° C. at a heating rate of 5° C. / min, kept at 1500° C. for 4 h, and cooled in the furnace to obtain a Ti-5Nb-15Ta-1.5Y alloy.
[0076] Comparative Example 1
[0077] The Ti-5Nb-15Ta alloy is obtained in the manner of Example 1 except that no YH2 powder is added.
[0078] The distribution of each element in the alloy obtained in Example 1 and Comparative Example 1 is as follows: Figure 1 As shown, Figure 1 (a) is the distribution of elements in Ti-Nb-Ta alloy without Y addition. Figure 1 (b) shows the distribution of elements in Ti-5Nb-15Ta-1.5Y alloy when 1.5wt.% YH2 is added. Figure 1 It can be seen that Y and O are distributed consistently. In addition to being locally aggregated, O is distributed in both the α phase and the β phase, with more in the α phase. Nb and Ta are mainly distributed in the β phase.
[0079] The oxygen content in the alloys obtained in Example 1 and Comparative Example 1 is as follows: Figure 2 As shown, the oxygen content is obtained by energy spectrum analysis under SEM, and the average value is calculated by multiple scans. Figure 2 It can be seen that compared with the alloy without YH2 addition, the solid dissolved oxygen content in the alloy is significantly reduced after adding YH2.
[0080] The quasi-static compressive mechanical properties of the alloys obtained in Example 1 and Comparative Example 1 at room temperature are as follows: Figure 3 As shown, Figure 3 It can be seen that by Figure 3It can be seen that compared with the alloy without YH2 addition, after adding YH2, the strength of the alloy remains almost unchanged, but the plasticity of the alloy is greatly improved.
[0081] Example 2
[0082] Alloy composition: Ti-6.64Al-31.09Nb-13.65Ta-1.5Ce-0.8La (mass fraction, %)
[0083] The preparation method adopts the following steps:
[0084] (1) Ti powder, Al-60Nb (mass fraction, %) master alloy powder, Nb powder, Ta powder and Al-47Ce-25La (mass fraction, %) alloy powder were weighed in proportion, and their mass percentages were as follows: Ti powder 46.7%, Al-Nb alloy powder 14.3%, Nb powder 22.5%, Ta powder 13.7%, Al-47Ce-25La alloy powder 3.2%, wherein the Ti powder particle size was 50 μm, the Al-60Nb alloy powder particle size was 50 μm, the Nb powder particle size was 15 μm, the Ta powder particle size was 20 μm, and the Al-47Ce-25La alloy powder particle size was 100 μm.
[0085] (2) Ar gas was used as the ball milling medium, and the volume ratio of the ball milling medium to the powder was 3:1. Ti powder, Al-60Nb alloy powder, Nb powder, Ta powder and Al-47Ce-25La alloy powder were fully mixed using a planetary ball mill at a speed of 200 r / min for 120 min.
[0086] (3) The powder obtained in step (2) is placed in a special rubber mold for cold isostatic pressing at a molding pressure of 350 MPa and a holding time of 30 min.
[0087] (4) The titanium alloy compact obtained in step (3) is placed in a sintering furnace for programmed heating, and the vacuum degree in the furnace is reduced to 3×10 -3 Pa, after the flowing Ar gas is introduced until the pressure in the furnace is stabilized at 101 kPa, the Ar gas flow rate is maintained at a constant value of 100 mL / min, and the green compact is heated from room temperature to 1200°C at a heating rate of 5°C / min;
[0088] In the flowing Ar atmosphere, the sample was heated from 1200° C. to 1450° C. at a heating rate of 3° C. / min, kept at 1450° C. for 3 h, and cooled in the furnace to obtain a Ti-6.64Al-31.09Nb-13.65Ta-1.5Ce-0.8La alloy.
[0089] Comparative Example 2
[0090] The method of Example 2 is followed, except that Al-47Ce-25La alloy powder is not added, and Ti powder, TiH2, AlNb alloy powder, elemental Nb and elemental Ta powder are mixed according to the component ratio to obtain Ti-6.74Al-31.56Nb-13.86Ta.
[0091] Figure 4 The distribution diagram of oxygen and other elements in the alloy obtained in Example 2 is shown in FIG. Figure 4 It can be seen that O aggregates where rare earth La and Ce are distributed, indicating that adding Al-La-Ce alloy powder can change the distribution of oxygen in the alloy.
[0092] Figure 5 is the static compressive stress-strain curve of the alloys obtained in Example 2 and Comparative Example 2, Figure 5 It can be seen that after adding Al-La-Ce alloy powder, the yield strength of the alloy decreases slightly, but the plasticity of the alloy is greatly improved.
[0093] Example 3
[0094] Alloy composition: Ti-6.7Al-31.37Nb-13.78Ta-1.32Y (mass fraction, %)
[0095] The preparation method adopts the following steps:
[0096] (1) Weigh Ti powder, Al-60Nb (mass fraction, %) master alloy powder, Nb powder, Ta powder and Y powder in proportion, the mass percentage of which is: Ti powder 46.8%, Al-Nb alloy powder 16.8%, Nb powder 21.3%, Ta powder 13.8%, rare earth element Y powder 1.3%, wherein the Ti powder particle size is 20 μm, the Al-60Nb alloy powder particle size is 50 μm, the Nb powder particle size is 10 μm, the Ta powder particle size is 5 μm, and the Y powder particle size is 50 μm.
[0097] (2) Ar gas was used as the ball milling medium, and the volume ratio of the ball milling medium to the powder was 5:1. Ti powder, Al-60Nb alloy powder, Nb powder, Ta powder and Y powder were fully mixed using a planetary ball mill at a speed of 1500 r / min for 60 min.
[0098] (3) The powder obtained in step (2) is placed in a special rubber mold for cold isostatic pressing at a molding pressure of 250 MPa and a holding time of 60 min.
[0099] (4) The titanium alloy compact obtained in step (3) is placed in a sintering furnace for programmed heating, and the vacuum degree in the furnace is reduced to 3×10 -3Pa, after the flowing Ar gas is introduced until the pressure in the furnace is stabilized at 101 kPa, the Ar gas flow rate is maintained at a constant value of 200 mL / min, and the green compact is heated from room temperature to 1200°C at a heating rate of 8°C / min;
[0100] In the flowing Ar atmosphere, the sample was heated from 1200° C. to 1550° C. at a heating rate of 2° C. / min, kept at 1550° C. for 2 h, and cooled in the furnace to obtain a Ti-6.7Al-31.37Nb-13.78Ta-1.32Y alloy.
[0101] Comparative Example 3
[0102] The method of Example 3 is followed, except that rare earth element Y powder is not added, to obtain Ti-6.74Al-31.56Nb-13.86Ta.
[0103] Figure 6 The distribution diagram of oxygen and other elements in the alloy obtained in Example 3 is shown in FIG. Figure 6 It can be seen that the distribution of rare earth Y and O is consistent, indicating that adding rare earth element Y has the same effect as adding rare earth hydride YH2, that is, adding rare earth element can change the distribution of oxygen in the alloy.
[0104] Figure 7 is the static compressive stress-strain curve of the alloy obtained in Example 3 and Comparative Example 3, Figure 7 It can be seen that after adding rare earth Y, the yield strength of the alloy decreases slightly, but the plasticity of the alloy is greatly improved.
[0105] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A low oxygen content Ti-Al-Ta-Nb alloy, characterized in that: In terms of mass percentage, the composition range of the low-oxygen Ti-Al-Ta-Nb alloy is Ti-(0-15)Al-(5-35)Nb-(5-20)Ta-(0-5)Ce-(0-5)Y-(0-5)La; the rare earth element content in the low-oxygen Ti-Al-Ta-Nb alloy is not 0 at the same time, and the total rare earth element content does not exceed 5% of the total mass of the alloy; The low oxygen content Ti-Al-Ta-Nb alloy comprises the following raw materials in percentage by weight:
2. The low oxygen content Ti-Al-Ta-Nb alloy according to claim 1, characterized in that: The particle size of the Ti powder is 20 to 50 μm; The particle size of the Nb powder is 5 to 20 μm; The particle size of the Ta powder is 5 to 20 μm.
3. The low oxygen content Ti-Al-Ta-Nb alloy according to claim 1 or 2, characterized in that: The mass content of Nb in the Al-Nb alloy powder is 50-70%, and the balance is Al; The particle size of the Al-Nb alloy powder is 20-50 μm.
4. The low oxygen content Ti-Al-Ta-Nb alloy according to claim 1, characterized in that: The rare earth hydride is one or more of YH3, YH2, LaH3, LaH2, CeH3 and CeH2; The particle size of the rare earth hydride powder is 10 to 100 μm.
5. The low oxygen content Ti-Al-Ta-Nb alloy according to claim 1 or 4, characterized in that: The rare earth element powder is one or more of Y powder, La powder and Ce powder; The particle size of the rare earth element powder is 10 to 100 μm.
6. The low oxygen content Ti-Al-Ta-Nb alloy according to claim 1, characterized in that: Calculated in percentage by mass, the Al-Ce-La alloy powder comprises: Ce: 40-50wt.%, Al: 20-30wt.%, and La: 20-30wt.%.
7. The low oxygen content Ti-Al-Ta-Nb alloy according to claim 1 or 6, characterized in that: The particle size of the Al-Ce-La alloy powder is 10 to 50 μm.
8. The method for preparing a Ti-Al-Ta-Nb alloy with low oxygen content according to any one of claims 1 to 7, characterized in that: The following steps are involved: The raw materials for preparing the low-oxygen content Ti-Al-Ta-Nb alloy are ball-milled and mixed to obtain a mixed powder; The mixed powder is subjected to cold isostatic pressing, programmed temperature sintering and cooling in sequence to obtain a Ti-Al-Ta-Nb alloy with low oxygen content.
9. The preparation method according to claim 8, characterized in that: The cold isostatic pressing pressure is 300-400 MPa, and the holding time is 20-60 min.
10. The preparation method according to claim 8, characterized in that: The programmed temperature sintering is carried out under a protective atmosphere; The temperature rising program of the programmed temperature rising sintering comprises: Raising the temperature from room temperature to a first temperature at a rate of 5 to 10°C / min; Raise the temperature from the first temperature to the sintering temperature at 2-5°C / min and keep the temperature; The first temperature is 1000-1200° C., the sintering temperature is 1300-1550° C., and the insulation time is 2-5 hours.